Comparative Efficacy and Safety of Intravenous Clonidine and Tramadol for Control of Postspinal Anesthesia Shivering - Vyas, Varsha (Anesth Essays Res, 2018)
BACKGROUND: Shivering is a common problem in patients undergoing surgery under spinal anesthesia. AIMS: The aim of this study was to compare efficacy and safety of clonidine versus tramadol in postspinal anesthesia shivering. SETTINGS AND DESIGN: This prospective, randomized, double-blind controlled clinical trial was conducted in a tertiary care setting. MATERIALS AND METHODS: A total of 60 American Society of Anesthesiologists physical status Class l and II adult patients (age 18–65 years) undergoing surgery under spinal anesthesia and developed shivering received either clonidine 1 μg/kg or tramadol 1 mg/kg intravenously. The time required for cessation of shivering, control and recurrence rate of shivering, effect on hemodynamics and side effects were compared between two groups. STATISTICAL ANALYSIS: Unpaired t-test and Chi-square test were used for comparison of continuous variables and dichotomous data between two groups, respectively. P < 0.05 was considered as statistically significant. RESULTS: Time for cessation of shivering was less in clonidine group than tramadol group (02.51 vs. 04.82 min; P < 0.001). Complete control of shivering was achieved in 80% of patients in clonidine group versus 70% in tramadol group. There was no significant difference for control (P = 0.5) and rate of recurrence of shivering between clonidine and tramadol group (06.7% vs. 16.7%; P = 0.42). Pulse rate and systolic blood pressure were significantly lower in clonidine group at 5 and 15 min as compared with tramadol. Significantly more number of patients experienced nausea and dizziness (36.7% vs. 0%; P < 0.001 and 20% vs. 0%; P = 0.01) with tramadol while bradycardia and hypotension were numerically more common in patients receiving clonidine (6.7% vs. 0% and 13.3% vs. 0%). CONCLUSION: Clonidine provides early relief from shivering than tramadol with fewer side effects in patients undergoing surgery under spinal anesthesia.